Architecture. - Lombardi, Sarah, 1972-; Danchin, Laurent, 1946-2017; Marini-Jeanneret, Pascale (Lausanne : l'Art Brut, 2015)
Catalogus van de tentoonstelling Architecture in de Art Brut Collection. We herkennen Scott Wilson, Willem van Genk, Augustin Lesage, Madge Gill, Adolf Wölfli, ...